Elevating CLIC4 in Multiple Cell Types Reveals a TGF- Dependent Induction of a Dominant Negative Smad7 Splice Variant. - Anjali Shukla; Yihan Yang; Sara Madanikia; Yan Ho; Mangmang Li; Vanesa Sanchez; Christophe Cataisson; Jing Huang; Stuart H Yuspa (PLoS ONE)
CLIC4 (Chloride intracellular channel 4) belongs to a family of putative intracellular chloride channel proteins expressed ubiquitously in multiple tissues. CLIC4 is predominantly soluble and traffics between the cytoplasm and nucleus and participates in cell cycle control and differentiation. Transforming growth factor beta (TGF-β) elevates CLIC4, which enhances TGF-β signaling through CLIC4 mediated stabilization of phospho-Smad2/3. CLIC4 is essential for TGF-β induced conversion of fibroblasts to myofibroblasts and expression of matrix proteins, signaling via the p38MAPK pathway. Therefore, regulation of TGF-β signaling is a major mechanism by which CLIC4 modifies normal growth and differentiation. We now report that elevated CLIC4 alters Smad7 function, a feedback inhibitor of the TGF-β pathway. Overexpression of CLIC4 in keratinocytes, mouse embryonic fibroblasts and other mouse and human cell types increases the expression of Smad7Δ, a novel truncated form of Smad7. The alternatively spliced Smad7Δ variant is missing 94bp in exon 4 of Smad 7 and is conserved between mouse and human cells. The deletion is predicted to lack the TGF-β signaling inhibitory MH2 domain of Smad7. Treatment with exogenous TGF-β1 also enhances expression of Smad7Δ that is amplified in the presence of CLIC4. While Smad7 expression inhibits TGF-β signaling, exogenously expressed Smad7Δ does not inhibit TGF-β signaling as determined by TGF-β dependent proliferation, reporter assays and phosphorylation of Smad proteins. Instead, exogenous Smad7Δ acts as a dominant negative inhibitor of Smad7, thus increasing TGF-β signaling. This discovery adds another dimension to the myriad ways by which CLIC4 modifies TGF-β signaling.